2019
DOI: 10.1590/s1678-9946201961018
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic factors and population dynamic of Aedes aegypti and Aedes albopictus in an endemic area of dengue in Brazil

Abstract: Aedes aegypti and Aedes albopictus are exotic species in the Americas with high epidemiological relevance as they are vectors of many pathogens. This study aimed at understanding the population dynamics of A. aegypti and A. albopictus and the influence of abiotic factors in an endemic area of dengue. The study was conducted in the urban area of Campo Grande, Mato Grosso do Sul, Brazil, over one year. In seven regions of the city, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 38 publications
0
23
0
2
Order By: Relevance
“…albopictus is present in all regions of the city and occurs throughout all months of the year. Despite the widespread distribution, oviposition analysis allowed identifying areas of greater infestation of Aedes sp, being sensitive also to detect increased oviposition in warmer and wetter months [6], indicating that this technique is useful for vector surveillance even in areas of high vector density, such as the city of Natal. Regarding the validity of using ovitraps in the surveillance routine, the study that compared the efficiency of several traps for capturing and collecting Aedes aegypti under field conditions found that ovitraps have the highest sensitivity and greatest association with climatic variations and consistently follow adult detection patterns caught in adult traps [31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…albopictus is present in all regions of the city and occurs throughout all months of the year. Despite the widespread distribution, oviposition analysis allowed identifying areas of greater infestation of Aedes sp, being sensitive also to detect increased oviposition in warmer and wetter months [6], indicating that this technique is useful for vector surveillance even in areas of high vector density, such as the city of Natal. Regarding the validity of using ovitraps in the surveillance routine, the study that compared the efficiency of several traps for capturing and collecting Aedes aegypti under field conditions found that ovitraps have the highest sensitivity and greatest association with climatic variations and consistently follow adult detection patterns caught in adult traps [31].…”
Section: Resultsmentioning
confidence: 99%
“…Abiotic factors such as temperature, humidity, wind and rainfall are determining factors that control the maintenance of these species. These climatic variables can affect oviposition, egg viability, larval development, longevity and adult dispersal [6]. In addition, socioeconomic factors such as uncoordinated urbanisation, lack of basic sanitation, irregular water distribution and incorrect waste management favoured the reproduction and dispersal of these vectors [7].…”
Section: Introductionmentioning
confidence: 99%
“…There, this mosquito is typically present in areas with dense vegetation but has colonized consistently anthropic areas [10,15]. Brazilian studies have described A. albopictus presence in urban areas with reminiscent forests [5,6,13,[16][17][18][19][20][21][22], in slums [15], in suburban areas [13,16], and in peridomicile and intradomicile location [16,23], evidencing its dispersion across sylvatic and urban settings [10,15] and its domestication [15]. The ability to use natural and artificial containers of water for breeding [9, 12, 15-18, 21, 24] supports this ecological plasticity [25].…”
Section: Introductionmentioning
confidence: 99%
“…These ndings together with results obtained by other authors about the ability of Ae. albopictus gravid females to disperse at least 800 meters [36][37][38], in addition to easily moving from areas with abundant vegetation to the urban area [38] and the nding of this specie in urban area [38,39] we consider it important to alert the National Control Program to strengthen the entomological monitoring of Ae. albopictus.…”
Section: Discussionmentioning
confidence: 99%